Interdisciplinary Expansions: Applying Recovery-Informed Theory to Interdisciplinary Areas of Recovery Science Research. Issue 4 (1st October 2020) - McDaniel, Jessica M.; Brown, Austin M.; Thompson Heller, Anne; Johnston, Teresa W.; Bergman, Brandon; Bohler, Robert; Brown, Tiffany; Eisenhart, Emily; Finch, Andrew; Harper, Kristen; Hart, Chris; Kimball, Thomas; et al.
ABSTRACT: To understand how persons with substance use disorders (SUDs) achieve and maintain wellness, it is necessary to expand recovery science research. The experiences of individuals in recovery are rarely reflected in SUD research which, at times, discounts subjective experiences of recovery. Recovery-informed theory (RIT) offers new lines of inquiry into various aspects of recovery, which may lead to innovative approaches to how SUDs are understood within clinical, professional, and community contexts. This paper reviews three preliminary areas to apply RIT: recovery measurement, identity processes, and systems engagement. Such advancement can impact the collective understanding of how individuals recover from SUD.